Isolation and Identification of Main Compounds of Lagochilus cabulicus - Saeidnia, S.; Barari, E.; Shakeri, A.; Gohari, A.R. (Asian Journal of Chemistry, 2012)
The genus, Lagochilus Bge., belongs to Lamiaceae family and consists of 44 species all over the world, 4 species of which are growing exclusively in Iran. Literature show that there is no report around the isolation and spectral elucidation of the main compounds of the Iranian species, Lagochilus cabulicus Benth. The aim of this study is to determine the main compounds of this species for the first time. Column and thin layer chromatographic methods were used for isolation and purification and spectroscopic data (1H NMR and 13C NMR) were employed for identification of the compounds isolated from ethyl acetate and methanol extracts. From the ethyl acetate and methanol extracts of L. cabulicus, four flavonoid, tricetin 3´-methyl ether (1), quercetin (2), quercetin 3-O-a-L-rhamnopyranosyl (1®6) b-D-glucopyranoside (3), quercetin 3-O-b-D-glucopyranoside (4), two steroids, sitosteryl acetate (5), stigmasteryl acetate (6) and one triterpene, lupeol (7), have been identified. The results show that the main compounds of L. cabulicus are biologically and pharmacologically active flavonol glucosides, sterol acetates and pentacyclic triterpene. There has not found any diterpene (lagochilin), as the main compound, in the aerial parts of L. cabulicus.